Kunci Kesuksesan UMKM di Era Pandemi: Analisis Kemampuan Adaptasi dan Kinerja - Gunarto, Muji; Tesa, Muniken (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: This study aims to determine the effect of adaptability on the performance of MSMEs in Ogan Komering Ulu (OKU) Regency during the Covid-19 period. Design/Methode/Approach: The research design used a survey approach to 350 respondents, namely MSMEs in OKU Regency. The analysis technique was carried out using a structural equation model (SEM) approach. Research Findings: This study's results found that adaptability significantly affects the performance of MSMEs in the OKU District. This means that the better adaptability of MSME actors will positively impact their business performance. Theoretical Contribution/ Originality: This research can provide new insights and valuable information to stakeholders in OKU District. Adaptability reflects the extent to which MSMEs are able to face changes in the external environment and change their business strategies responsively. Focusing on this variable can provide a deeper understanding of how MSMEs can survive and thrive in changing situations. Practitionel/Policy implication: The government and other stakeholders can use the results of this research to provide better resources and support to MSMEs in OKU District. This kind of support can help MSMEs in developing their adaptability and improve their overall business performance. Research limitation: Although this study demonstrates a relationship between adaptability and MSME performance, it should be noted that observational studies such as this one cannot establish a direct cause-and-effect relationship. Even though there is a strong statistical relationship between the variables studied, there may be other unmeasured factors influencing the relationship. Therefore, it is necessary to carry out further research, such as experiments or longitudinal research, to better understand the nature of the causality between adaptability and MSME performance.